2020
DOI: 10.1002/slct.201904399
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone‐Assisted Sensitive, Selective and Reversible Recognition of Copper Ions in an Aqueous Medium

Abstract: A photochromic substituted spiropyran (8-methoxy-1,3',3'trimethylspiro[chromene-2,2'indoline]) was successfully synthesized and its structural integrity was ascertained using spectroscopic methods. Owing to the uniquely positioned methoxy and phenolic groups for potential coordination with a metal ion, it was investigated for the recognition of toxic metal ions. The spiropyran derivative responded to the presence of Cu 2 + ions in an aqueous solution by displaying a color change visible to the naked eye (color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The color change can be easily analyzed by taking digital images using frequently available smartphones. The digital images can be analyzed for change in intensity based on RGB color space along with hue and saturation, which on analysis can be used as a digital optical signal for concentration analysis [27b,29,37] . To exploit the alteration in color on paper strips caused by cyanide ion, test strips of probe 1 were soaked in solutions of cyanide ions having different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The color change can be easily analyzed by taking digital images using frequently available smartphones. The digital images can be analyzed for change in intensity based on RGB color space along with hue and saturation, which on analysis can be used as a digital optical signal for concentration analysis [27b,29,37] . To exploit the alteration in color on paper strips caused by cyanide ion, test strips of probe 1 were soaked in solutions of cyanide ions having different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another advantage is that the digital camera on smartphones is used by almost many people so this method is easy and fast [14]. Research on digital image colorimetry on smartphones for chemical analysis has shown great interest in recent years, such as the analysis of metals Hg 2+ [15], Cu 2+ [16], paraoxon herbicides [17], methyl parathion pesticides [18], and tetracycline [19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of images obtained from digital devices and their processing to obtain the color modes (e. g. RGB, HSV, CMYK, and grayscale) has been successfully explored for the determination of Ca 2 + , Co 2 + , Cr 6 + , Cu 2 + , Hg 2 + , Fe 3 + , Fe 2 + , Mg 2 + and Pb 2 + in colored solutions from water, [16][17][18][19][20][21] alcoholic beverages, [22][23][24][25] foodstuffs, [21,[26][27] soils, [20] and biodiesel [28] samples. These methods are attractive due to their simplicity, inexpensiveness, high sample throughput, and possible portability.…”
Section: Introductionmentioning
confidence: 99%